An analysis of computerized accounting system security threats in Malaysian public listed companies / Mahlindayu Tarmidi @ Tokhid, Azwan Abdul Rashid and Wan Mohamad Taufik Wan Abdullah - Tarmidi @ Tokhid, Mahlindayu; Abdul Rashid, Azwan; Wan Abdullah, Wan Mohamad Taufik (2012)
Numbers of incidents pertaining data errors, system breach, violation of internal control and manipulation of financial information had raised the organization attention and concern. Organizations are consequently more aware of the security and integrity issues in regards of the computerized accounting system and the need to take appropriate action. This research is to investigate the security threats issues in computerized accounting system in Malaysian public listed companies. Through questionnaires to 500 companies, the study is expected to determine the companies' most important perceived security threats, and variations among the industries and organization size. The empirical evidence may enable organizations to evaluate their computerized accounting system security, and begin to properly pursue effective strategies to improve quality and lower risk.